2004
DOI: 10.1002/hbm.20024
|View full text |Cite
|
Sign up to set email alerts
|

EEG‐fMRI of focal epileptic spikes: Analysis with multiple haemodynamic functions and comparison with gadolinium‐enhanced MR angiograms

Abstract: Combined EEG-fMRI has recently been used to explore the BOLD responses to interictal epileptiform discharges. This study examines whether misspecification of the form of the haemodynamic response function (HRF) results in significant fMRI responses being missed in the statistical analysis. EEG-fMRI data from 31 patients with focal epilepsy were analysed with four HRFs peaking from 3 to 9 sec after each interictal event, in addition to a standard HRF that peaked after 5.4 sec. In four patients, fMRI responses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
210
2
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 211 publications
(230 citation statements)
references
References 45 publications
11
210
2
7
Order By: Relevance
“…On the other hand, restricting the HRF to the canonical shape, such as in the standard GLM method, may prevent the detection of real activations. For example, various studies have observed HRFs with late peaks (Bagshaw et al, 2004;Jacobs et al, 2008) or even early HRFs preceding the observed EEG events (Hawco et al, 2007;Jacobs et al, 2009;Moeller et al, 2008). Simulations have shown that HRFs delayed by only a few seconds may be undetected by the GLM (LeVan and ).…”
Section: Methodological Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, restricting the HRF to the canonical shape, such as in the standard GLM method, may prevent the detection of real activations. For example, various studies have observed HRFs with late peaks (Bagshaw et al, 2004;Jacobs et al, 2008) or even early HRFs preceding the observed EEG events (Hawco et al, 2007;Jacobs et al, 2009;Moeller et al, 2008). Simulations have shown that HRFs delayed by only a few seconds may be undetected by the GLM (LeVan and ).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…The 6 motion parameters (3 translations and 3 rotations) were also incorporated as confounds, since residual motion artifacts may contaminate the fMRI images even after motion correction (Friston et al, 1996). The BOLD changes related to the seizures were modeled as boxcar functions based on the timing and duration of the marked events, and convolved with four HRFs peaking at 3, 5, 7, and 9 s (Bagshaw et al, 2004). If the scanning session included interictal events, additional regressors were formed in the same way and treated as confounds in the model.…”
Section: Glm Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that the actual HRF varies depending on the brain region, individual and time of the recording (Aguirre et al, 1998). The use of multiple HRFs (Bagshaw et al, 2004) and patient-specific HRFs (Kang et al, 2003) in EEG-fMRI indeed is more sensitive to detect positive and negative BOLD responses that would be otherwise missed with the standard model. We improved the sensitivity of EEG-fMRI with the use of four different HRFs (peaking at 3, 5, 7 and 9 s) in a group of children with symptomatic epilepsy (Jacobs et al, 2006), and as in adults, the responses seem to be specific, as demonstrated by their concordance with the anatomical areas related to the generation of the spikes, as well as with the potentially epileptogenic lesion/region.…”
Section: Introductionmentioning
confidence: 99%
“…Considering a probable small lag between real onset and time to declare for patients who reported auras without surface EEG correlate, several GLM analyses were performed after moving the onsets backward in time (Bagshaw et al, 2004), relative to the fNIRS signals, by multiples of 4 s.…”
Section: Discussionmentioning
confidence: 99%